Pengelolaan Sampah Organik Di Industri Galangan Kapal Dengan Metode Komposting Menggunakan Aktivator Ecoenzymes & Effective Microorganism 4 (EM4) - Lady Sion Simanullang; Syadzadhiya Qothrunada Zakiyayasin Nisa (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
The shipbuilding industry produces organic and inorganic waste. The organic waste produced by the shipbuilding industry is dry leaves, dry grass, dry wood and other dry materials. Organic waste management is becoming increasingly important in this industry because the industry's very rapid growth has the potential to increase negative environmental impacts if not handled properly. Utilizing organic waste into fertilizer is an activity that can be carried out with the aim of reducing waste around the shipyard industrial environment. This organic fertilizer is made using a simple composting method so that it can be applied in this industry. The composting process involves 2 different treatments, namely the first is an activator solution in the form of a mixture of ecoenzymes, water and sugar solution and the second is using Effective Microorganism 4 (EM 4). The results of the research showed that these two treatments produced a pH that was not much different, namely 6.9 for EM4 and a pH of 7 for the ecoenzymes activator. The temperature of the compost produced in the ecoenzymes mixture treatment was 300C and in the EM4 treatment was 300C. This shows that the activity of decomposing microorganisms is running well.